ETHICS AND THE MORAL RESPONSIBILITIES OF POWER IN THE PHILOSOPHY OF ZAHIRIDDIN MUHAMMAD BABUR - Khamdamov Bekhzod Khabibovich (Innovate Conferences, 2025)
The legacy of Zahiriddin Muhammad Babur (1483–1530) is most commonly framed in political and military terms — as the founder of the Mughal Empire, a skilled general, and a cultural innovator. Yet beneath the conquests and chronicles lies a powerful, reflective philosophy of governance shaped by ethics, introspection, and a deeply personal understanding of justice. Babur’s writings, especially the Baburnama, reveal a ruler who saw leadership as a moral responsibility entrusted by God, and who believed that power must be regulated by ethical principles, self-awareness, and spiritual accountability.